2000
DOI: 10.1161/01.str.31.2.526
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Endothelin-1–Induced Contraction in Rabbit Basilar Artery

Abstract: Background and Purpose-Endothelin-1 (ET-1) is suggested to be a major cause of cerebral vasospasm after subarachnoid hemorrhage. However, the mechanism of ET-1-induced contraction in cerebral arteries remains unclear. This study was undertaken to demonstrate the possible role of protein tyrosine kinase (PTK), mitogen-activated protein kinase (MAPK), and protein kinase C (PKC) in ET-1-induced contraction. Methods-PD-98059, damnacanthal, wortmannin, AG-490, genistein, calphostin C, and staurosporine were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 39 publications
5
55
1
Order By: Relevance
“…p42 / p44 MAPK may play a role in vascular smooth muscle contraction (11). Moreover, p42 / p44 MAPK may be an important regulator for rabbit basilar artery contraction (12). In contrast, p42 / p44 MAPK is † These authors contributed equally to this work.…”
Section: +mentioning
confidence: 99%
“…p42 / p44 MAPK may play a role in vascular smooth muscle contraction (11). Moreover, p42 / p44 MAPK may be an important regulator for rabbit basilar artery contraction (12). In contrast, p42 / p44 MAPK is † These authors contributed equally to this work.…”
Section: +mentioning
confidence: 99%
“…Since class IB PI3-kinase ␥ regulates Ras-MAP kinase pathway and PI3-kinase inhibitor can attenuate ET-1-induced contraction and ET-1-induced MAP kinase activity, 12 class IB PI3-kinase ␥ may be involved in early vasospasm (which was not studied in the present study) by regulating Ras-MAP kinase. Thus, the time course of PI3-kinase activation during cerebral vasospasm, especially in the early stage, requires further investigation.…”
Section: Pi3-kinase and Vasospasmmentioning
confidence: 83%
“…37 PI3-kinase inhibitor also reduces angiotensin AT 1A receptor-stimulated and G␤␥ complexes-stimulated L-type Ca 2ϩ channel current in venous myocytes. 38 PI3-kinase inhibitors attenuate smooth muscle contraction induced by many G protein-coupled receptor agonists 12,14,16 and growth factors. 16 It is reported that PI3-kinase may act either downstream 39,40 or upstream from Ras protein in the signal transduction pathways.…”
Section: Pi3-kinase and Vasospasmmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of endothelin-1 to produce pathological changes of cerebral arteries after subarachnoid haemorrhage has been well studied (Asano et al 1990;Suzuki et al 1990;Caner et al 1996;Lampl et al 1997;Suzuki et al 2000;Yakubu et al 2000;Zubkov et al 2000), however, the details regarding its participation remain to be clarified. Previous studies (Dallaire et al 1992;Stanimirovic et al 1994;Nie & Olsson 1996;Dehouck et al 1997;Hernández et al 2000) have already noted and tried to examine the role of endothelin-1 in disrupting bloodbrain barrier permeability, but convincing evidence on the underlying mechanism has not been offered.…”
mentioning
confidence: 99%